Synthesis and pH Sensitive Fluorescent Performance of 2＇-Chloroseminaphthofluorescein with Dual Bands - 葛凤燕 陈立功 杨雪 袁帅 (东华大学学报（英文版）, 2017)
A novel unsymmetrical fluorescein derivative substituted by chlorine and naphthol, 2 ＇-chloroseminaphthofluorescein, was prepared by the two-step synthetic method. This method can effectively control the reactive process,so the pure unsymmetrical fluorescein derivative can be obtained in high yield. The new fluorophore exhibited dual absorption bands,dual excitation bands and dual emission bands with long-wavelength,selectively exciting the acidic and basic forms of the fluorophore. Compared with the similar symmetrical fluorescein derivatives such as 2 ＇, 7 ＇-dichlorofluorescein and dinaphtofluorescein, this fluorophore was found to have larger Stokes shift,especially in the basic form. Based on the properties above,this unsymmetrical fluorescein derivative is expected as a good fluorescent probe to be used where the interference exists due to the presence of endogenous fluorescers.